Mapping the Evolution of Cultural and Problem-Based Approaches in Mathematics Education: A Bibliometric Review from 2000 to 2024 - Mailili, Wahyuni; Ijirana, Ijirana; Rizall, Muhammad; Hadi, Windia (FKIP Universitas Lampung, 2025)
This study is a literature review that aims to analyze research trends on Problem-Based Learning (PBL), Mathematical Communication, Ethnomathematics, and Problem Solving in mathematics education, and to provide recommendations for variables with potential for future research. Bibliometric analysis was used to identify relevant research articles. Search data were obtained from Google Scholar from 2000 to 2024 using the keywords problem-based learning, mathematical communication, ethnomathematics, and problem solving, with publication types limited to journals, articles, and conference papers. From a total of 72 articles initially screened, the refinement process yielded 52 relevant articles published between 2007 and 2024. To analyze the data comprehensively and achieve the research objectives, data analysis was conducted using Harzing's Publish or Perish, Excel, and VOSviewer. The benefit of this research is that it can help researchers who will conduct further research on problem-based learning, mathematical communication, ethnomathematics, and problem-solving by identifying the opportunities identified in this study. The results of this study show a continuous and developing research trend and provide recommendations for variables that have the potential to be studied in the future related to the integration of the keywords problem-based learning, ethnomathematics, and mathematical communication as a proposed strategic approach to simultaneously strengthen mathematical literacy and mathematical problem-solving skills in the context of modern learning. This study is expected to provide a roadmap and outline new opportunities for researchers interested in exploring topics related to the keywords, serve as an important reference, and inspire new research with greater novelty, thereby supporting the development of 21st-century skills through mathematics education. Keywords: problem-based learning, mathematical communication, ethnomathematics, problem solving, bibliometric analysis, VOSviewer.